Introduction: Visual Anthropology in the Middle East. Issue 1 (1st June 2019) - Hertzog, Esther; Katzir, Yael
Abstract : This issue demonstrates the potential and unique contribution of visual anthropology to deepening and expanding anthropological knowledge with historical, artistic, cultural and political perspectives. Describing and analysing historical events, daily social life and the arts, the articles offer original interpretations of human experiences and social processes that are part of the Middle East reality, in the past and present. Some authors suggest striving to establish ethnic, cultural and national identities goes hand in hand with struggles for civilian rights and socio-economic equality. Using illustrations and a feminist analysis, other authors reflect on women's marginalisation in the arts and in the historiography of this region. The use of visual materials, highlighting similarities among divergent communities, entails an optimistic view about the potential contribution of arts to break through fundamental dividing features.